ADAMTS4 and ADAMTS5 may be considered as new molecular therapeutic targets for cartilage damages with Kashin-Beck Disease. (February 2020) - Meng, Peilin; Zhang, Feng'e; Zhang, Yanan; Wei, Haiyan; Tan, SiJia; Guo, Xiong; Wang, Sen; Yu, Yan
Abstract: There are a pretty number of research demonstrating that ADAMTS4 and ADAMTS5 playing primary roles in the degradation of cartilage during inflammatory joint diseases like osteoarthritis (OA). Because Kashin-Beck Disease (KBD) has been found to own the common pathological changes and symptoms with OA, and is regarded as the specific type of osteoarthritis, it's reasonable to believe that ADAMTS4 and ADAMTS5 may exert an enormous functions on the injury of cartilage of the KBD and may be potential molecular therapeutic targets for KBD.